ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KECELAKAAN DI SAMARINDA - Wiyadi Wiyadi; Ratanto Ratanto (MNJ (Mahakam Nursing Journal), 2018)
Preliminary. Traffic Accident is an unexpected and accidental event on the Road involving a Vehicle with or without other road users that result in human casualties and / or property losses.. Traffic accidents are the first cause of death in adolescents aged 15-29 years in the world and around 1.25 million deaths due to accidents worldwide in 2013 and the number settled since 2007.The purpose of this study was to analyze factors related to the incidence of traffic accidents in Samarinda city. Method. The design of this study is a description with a cross sectional approach. As for sampling, the total sample was 83. The researcher took notes on the BAP (Police investigation report ) accident at Samarinda Police Station , Satlantas.department. The results : The result of the Chi Square test showed that between the age factor and the incidence of accidents in Samarinda, is at p = 0.45, between the sexes and the incidence of accidents is P = 0.390, between the factors of negligence with the incidence of accidents is P = 0.015 , between factor of illness with the incidence of accidents is P = 0.84, and between factors not orderly with the incidence of accidents. P = 0.014 The conclusion in this study there is no relationship between the factors of gender, age and type of accident with the accident in Samarinda. There is a relationship between factors of negligence and not orderly with traffic accident events in Samarinda